The static performance effect of hybrid-hierarchical interconnection by shifted completely connected network - Ali, Mohammed N.M.; Hafizur Rahman, M. M.; Abubakar, Adamu; Yasushi, Inoguchi; Eklas, Hossain (IEEE, 2021)
Massively parallel computer (MPC) systems execute many operations based on internal networks called interconnection networks. The performance of these networks is affected by their topolo- gies.There are many topologies of interconnection networks for MPC systems, unfortunately, they faced many drawbacks. Expanding the size of the network degrades the performance of these topologies. That is why this current paper presents a hybrid-hierarchical interconnection network (HIN) topology by Shifted Completely Connected Network (SCCN) to circumvent the drawbacks of the existing topologies. An experimental evaluation involving the design and development of a hierarchical network was carried out. A two-dimensional higher level networks has been produced and its static network performance parameters evaluated through simulators. The nding of the simulations has shown some good performances compared to many previous designed networks. SCCN is better than all conventional networks in terms of diameter, cost and average distance.